THE EFFECTIVENESS OF BLENDED LEARNING IN-TEXT LEARNING OBSERVATION REPORT ON CLASS VI SD STUDENTS - Nugraha, Via; Sobur, Asep Muhamad; Sapdiani, Ratih (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This research was made because of the condition of distance learning which must also be effective in achieving learning objectives. Meanwhile, distance learning that is carried out suddenly makes teachers not maximal in planning and choosing the right method. For this reason, this study tries to implement balanced learning during distance learning with the following objectives: 1) making blanded leaning learning scenarios, and 2) implementing these scenarios in the material of writing an observation report text for grade VI SD. The research method used is qualitative, which describes the phenomenon under study as a whole without seeing any relationship between certain variables. The population used was 110 grade 6 students of SD 010 Cidadap. From this population, 28 students were taken as the research sample. The research was conducted by observing the learning process both online and face-to-face. These observations are also processed data to determine the results of the research. The results showed that the scenario was made based on blended learning, namely two meetings in the network and two face-to-face meetings with attention to pandemic conditions and health protocols. The effectiveness of the implementation was seen based on the observation of each meeting and the writing results of the students who were 85% able to absorb the material well.